Ambient‐Light‐Promoted Perfluoroalkylative Cyclization of β, γ‐Unsaturated Hydrazones: Synthesis of Perfluoroalkylated Pyrazolines. Issue 40 (26th October 2017) - Yu, Jing‐miao; Cai, Chun
Abstract : An ambient‐light‐promoted, metal‐free strategy for the direct perfluoroalkylative cyclization of β, γ‐unsaturated hydrazones was developed. The radical process allowed the multifunctionalization of β, γ‐unsaturated hydrazones and selectively yielded perfluoroalkylated pyrazolines in good to excellent yields. The reaction was performed in the presence of a wide range of functional groups under mild reaction conditions and was operationally simple. Abstract : An ambient‐light‐promoted, metal‐free strategy for the direct perfluoroalkylative cyclization of β, γ‐unsaturated hydrazones is reported. This radical process has wide functional‐group tolerance, is performed under mild reaction conditions, and is operationally simple. The perfluoroalkylated pyrazoline products are obtained in good to excellent yields. TMG = 1, 1, 3, 3‐tetramethylguanidine.